2001
DOI: 10.1111/j.1749-6632.2001.tb03623.x
|View full text |Cite
|
Sign up to set email alerts
|

The Action of Acetyl‐l‐Carnitine on the Neurotoxicity Evoked by Amyloid Fragments and Peroxide on Primary Rat Cortical Neurones

Abstract: The amyloid β‐peptides have been implicated in the excitotoxic mechanism of neuronal injury in the pathogenesis of Alzheimer's disease. In this paper we examine the effect of different amyloid fragments (β A1–40, A1–28, and A25–35), as well as potential neuroprotective compounds on rat cortical neuron viability. Exposure of neurones to β A25–35 or A1–40 at concentrations as low as 1 μg/ml inhibited, significantly, the MTT response and this level of inhibition was similar after 24‐h or three‐day exposure. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…Once inside the mitochondrial matrix, ALCAR is converted to acetyl CoA and free carnitine via carnitine acyl transferases [24]. Numerous reports show neuroprotective effects of exogenous ALCAR in a number of neurologic disorders [22,25,26,27,28,29,30]. Supraphysiologic levels of exogenously administered ALCAR provide neuroprotection in animal models of neurodegenerative diseases and acute neurologic injury paradigms [22,23,24,31].…”
Section: Introductionmentioning
confidence: 99%
“…Once inside the mitochondrial matrix, ALCAR is converted to acetyl CoA and free carnitine via carnitine acyl transferases [24]. Numerous reports show neuroprotective effects of exogenous ALCAR in a number of neurologic disorders [22,25,26,27,28,29,30]. Supraphysiologic levels of exogenously administered ALCAR provide neuroprotection in animal models of neurodegenerative diseases and acute neurologic injury paradigms [22,23,24,31].…”
Section: Introductionmentioning
confidence: 99%
“…S radical production by MPTP Unlike salicylic acid (Kuhn et al, 1995), ALCAR is not known to have any scavenging effect on HO S radical (Virmani et al, 2001). Thus its ability to prevent the production of HO S radicals must lie at another level.…”
Section: Possible Mechanisms Of Alcar In Preventing Homentioning
confidence: 94%
“…Previous studies in heart and brain showed that dietary supplementation with a blend of n-3 FA and carnitine/ALC was associated with (a) extensive changes in the activities of key enzymes in the mitochondria [33], (b) improved recovery of mitochondrial energy metabolism [57], (c) increased n-3 FA content of mitochondrial membranes [58], and subsequent improvement in mitochondrial Ca 2+ flux and Ca 2+ -dependent processes [34], as well as (d) improvement of lipid metabolism [59, 60]. Taking these findings together with our findings we assume that beneficial effects of Phototrop on visual functions in early AMD may come from the synergetic action of ALC, n-3 FA, and CoQ10 on mitochondrial functions.…”
Section: Discussionmentioning
confidence: 99%